ESCUTA MUSICAL: um experimento de diferenças e territórios existenciais – hibridismo e Sul Global na música pop - CARVALHO, NILTON FARIA DE (2021)
This work embraces the communicational experience of popular music through the analysis involving musical listening of works with a hybrid and more experimental profile. The empirical front of the research collected data in music listening workshops conducted in two high schools as an extension activity. The songs used (corpus) differ from the regimes of pop music in the media, centered on market parameters of the West, as they value semiotic, cultural borderlines, and aesthetics of the Global South. The theoretical-methodological path, therefore, will: a) identify the recognition regimes and the paradigms of pop music; b) review notions about musical genres to understand them in their dialogical/enunciative, intertextual, and of cultural boundaries micro process; c) understand hybridizations and experimentalisms as radical moments of these semiotic processes; d) to collect the empirical material in the music listening workshops by the narrative research method; e) and to analyze the communicational experience, in the end, with contributions from the semiotics of culture, the theories of affection, notions of materialities of communication, and post-structuralist and decolonial concepts. It is an epistemological and ontological clash, in the media sensory scope, mobilized by an aesthetic experiment that reviews music in the media and its existential territories. The interdisciplinary Communication/Education dialogue suggests the use of popular music in activities of learning, creation, reflection, and production of knowledge and defends the need to rethink our relations with memory and media environments